Productivity improvement via simulation method (Manufacturing industry) - Hasbullah, Mat Isa (2010)
Productivity improvement plays an important role in determining whether a company can survive in the future based on customer demands that it can fulfill. In this respect, simulation can be utilized as a what-if analysis tool to decide which productivity improvement strategies to be adopted. This thesis presents a simulation of the current performance of outputs and profits using WITNESS simulation software. The main objective of this project is to demonstrate the use of simulation in analyzing the existing production floor performance and in evaluating various alternatives to overcome the existing problem. This project is conducted in an electronic connector manufacturing company located in Shah Alam, Selangor. The production line involved in this project is the assembly line for FX15 model while the product involved in this study is connector manufactured. First, a simulation study on the existing production line is carried out to evaluate the production floor performance. Results of the study revealed that the current production floor was suffering from time working handling. From here, a total of 3 alternative layouts were proposed and they were simulated to determine their effect on the production performance. One way ANOVA test with multiple comparisons was conducted to select the best result. The results again showed a significant difference between each alternative layout and the best alternative to improve the existing production line is the Alternative layout III with productivity increment of 9.15% higher the current situation.